Clinical and Epidemiological Study on Tubercular Uveitis in a Tertiary Eye Care Centre in Italy. (23rd March 2020) - La Cava, M.; Bruscolini, A.; Sacchetti, M.; Pirraglia, M. P.; Moramarco, A.; Marenco, M.; Iaiani, G.; Covelli, G.; Rizzo, T.; Abicca, I.; Lambiase, A.
Abstract : Purpose . To describe frequency, clinical characteristics, and visual prognosis of tubercular uveitis (TBU) in a nonendemic country. Methods . We retrospectively reviewed 3743 charts of patients with endogenous uveitis visited from 2008 to 2018 at a tertiary referral centre in Rome, Italy. We included immunocompetent patients with diagnosis of TBU. Patients were divided in two groups: patients with history of uveitis without a previous diagnosis of TBU (group A) and patients at their first episode of TB uveitis (group B). Results . TBU was diagnosed in 28 (0.75%) out of 3743 patients. Twelve (42.9%) patients came from tuberculosis endemic areas. All patients received specific antitubercular treatment (ATT) and were evaluated for a mean follow-up of 3.2 ± 2.9 years. Group A showed a greater number of ocular complications when compared with group B. ATT was effective in reducing the frequency of recurrences of uveitis in patients of group B. Conclusion . Intraocular inflammation can be the first manifestation of tuberculosis. Our data highlight that early diagnosis and specific treatment of TBU may allow to decrease recurrences and to improve visual outcomes.